2021
DOI: 10.3390/foods10051046
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Cell Count in Goat Milk: An Indirect Quality Indicator

Abstract: A high somatic cell count (SCC) impacts dairy quality to a large extent. The goal of this work was to investigate differences in goat milk composition and technological parameters according to SCC cut-off (600, 700, 800, and 1000.103/mL). Thirty-four individual milk samples of White Shorthair goats in a similar stage of lactation were investigated. The first differences in milk quality appeared already at SCC cut-off of 600.103/mL (5.58 LSCS-linear somatic cell score), yet the most striking differences were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
18

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 30 publications
2
12
1
18
Order By: Relevance
“…The EC from goat milk observed in the study was substantially lower than reported by other authors (42,46). All analyzed microbiological and physicochemical parameters of goat milk are shown to be crucial for qualitative and safe cheese production under small scale farms (12,39,42,47).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The EC from goat milk observed in the study was substantially lower than reported by other authors (42,46). All analyzed microbiological and physicochemical parameters of goat milk are shown to be crucial for qualitative and safe cheese production under small scale farms (12,39,42,47).…”
Section: Discussioncontrasting
confidence: 55%
“…According to Moroni et al (38), who conducted goat milk quality monitoring program in Northern Italy, similar results for SC number was observed in positive bacteriological samples (5.6 cells/ml), while for negative bacteriological samples, these authors reported a significantly lower number of SC (3.9 cells/ml). However, in a study performed by Podhorecka et al (39), a higher number of SC were counted in goats free of mastitis-causing bacteria (MCB), highlighting again the need for determination of standards for the number of SC, which are difficult to interpret in goats (25,27).…”
Section: Discussionmentioning
confidence: 99%
“…The varying feed temperatures at 20, 30, 40, and 50°C had an effect on the GWOBs' microfiltration (0.2 m) in comparison to the standard LTLT procedure (63°C/30 min). to maintain homogeneity, volatile ingredients, and useful properties, and to generate a higher quality microbial population, it is recommended that GWOB be processed at ideal temperatures of 30°-40°C (Podhorecká et. al., 2021).…”
Section: Microfiltration Treatmentmentioning
confidence: 99%
“…This is due to the increased need for processed meals to have more nutritional value and fresh-like qualities. According to the findings, monopolar PEF pasteurization can be recommended to enhance the quality of goat milk at the industrial level (Podhorecká et. al., 2021).…”
Section: Pulse Electric Field Treatmentmentioning
confidence: 99%
“…The findings indicated that even a lower value of SSC can have a substantial effect on goat milk's technological features. The routine screening of SSC should be exhibited and reported to dairy manufacturers to ensure the consumer receives a high-quality end product ( 19 ).…”
Section: Introductionmentioning
confidence: 99%